Pengaruh Likuiditas, Profitabilitas, Struktur Modal, dan Biaya Operasional Perusahaan terhadap Pajak Penghasilan Badan: (Studi Empiris pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Tuti Tuti; Rinny Meidiyustiani (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This study aims to determine the effect of liquidity, profitability, capital structure, and company operating costs on corporate income tax. The population in this study is property and real estate sector companies listed on the Indonesia Stock Exchange in the financial statements for the 2019-2023 period. The sampling technique in this study used the purposive sampling method and obtained samples from 50 companies. The analysis techniques used are multiple linear regression analysis using SPSS software version 26.0. The results of this study show that Liquidity has a negative and significant influence on Corporate Income Tax, Profitability not significantly influential on Corporate Income Tax, Capital Structure not significantly influential on Corporate Income Tax. Company Operating Cost has a positif and significant influence on Corporate Income Tax.